Genetic characterization of hull color using BSR-Seq and genome re-sequencing approaches in foxtail millet - Tian, Bohong; Zhang, Lixin; Hu, Jinghuang; Liu, Yanli; Zhou, Lulu; Ping, Wenchao; Zou, Jingwei; Li, Hongjie (Frontiers in Plant Science, 2022)
Hull color of foxtail millet is an important indicator of certain nutritional quality parameters. An F2:6 recombinant inbred line (RIL) population developed by crossing a yellow-hulled cultivar Yugu 5 and a brown-hulled cultivar Jigu 31 was used to determine the genetic control of the hull color trait. This population segregated for yellow and brown hull colors in a ratio of 2:1, indicating that hull color is regulated by multiple genetic loci. A bulk segregant analysis-RNA sequencing (BSR-Seq) approach performed using the RNA bulks from 30 lines with brown and yellow hull colors each identified three genomic regions on chromosomes 1 (4,570,517-10,698,955 bp), 2 (40,301,380-46,168,003 bp), and 3 (44,469,860-50,532,757 bp). A new QTL for brown hull color of Jigu 31, QHC.czas1, was detected between bin markers Block43 and Block697 on chromosome 1 with the genetic linkage map constructed by re-sequencing a subset of the 147 RILs. This QTL explained a high level of phenotypic variation ranging from 28.0% to 47.0%. The corresponding genomic region of this QTL in the foxtail millet reference genome overlapped with that detected on chromosome 1 by the BSR-Seq analysis. Nineteen genes associated with biosynthesis of anthocyanin were annotated in this genomic region. Gene Si1g06530 encoding a SANT/Myb domain protein was highly expressed in developing panicles and seeds, which warrants further verification as the candidate gene for the brown color hull of Jigu 31. Moreover, several annotated genes for biosynthesis of anthocyanin were identified in the genomic regions of chromosomes 2 and 3.